ADRENERGIC AND CALCIUM REGULATION OF CONTRACTILITY OF NEONATAL RAT CARDIOMYOCYTES IN CULTURE (International conference on multidisciplinary science, 2025)
The study demonstrated that activation of the adrenergic system leads to an increase in the frequency of contractions due to stimulation of bisoprolol-sensitive β₁-adrenoreceptors. In addition, neonatal cardiomyocytes demonstrated differential response to the calcium channel antagonist’s verapamil and nifedipine.